2012
DOI: 10.1530/jme-12-0182
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid pathway and the female reproductive organs

Abstract: Endocannabinoids are endogenous ligands of cannabinoid, vanilloid and peroxisome proliferator-activated receptors that activate multiple signal transduction pathways. Together with their receptor and the enzymes responsible for their synthesis and degradation, these compounds constitute the endocannabinoid system that has been recently shown to play, in humans, an important role in modulating several central and peripheral functions including reproduction. Given the relevance of the system, drugs that are able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 75 publications
(58 reference statements)
0
28
0
1
Order By: Relevance
“…The dysfunction of FAAH could affect the AEA or 2-AG levels in the uterus, leading to negative effect on pregnancy outcome ( 26 ). In the menstrual cycle, the FAAH activity in peripheral blood mononuclear cells at the luteal phase (the window of implantation, day 21) was higher than the FAAH activity at other phases, whereas the AEA level was low ( 27 ). Others reported that low activity of FAAH and high AEA level were associated with the pregnancy loss after IVF-ET (IVF and embryo transfer) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction of FAAH could affect the AEA or 2-AG levels in the uterus, leading to negative effect on pregnancy outcome ( 26 ). In the menstrual cycle, the FAAH activity in peripheral blood mononuclear cells at the luteal phase (the window of implantation, day 21) was higher than the FAAH activity at other phases, whereas the AEA level was low ( 27 ). Others reported that low activity of FAAH and high AEA level were associated with the pregnancy loss after IVF-ET (IVF and embryo transfer) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Au niveau hypophysaire, la pré sence de ré cepteurs CB1 suggè re un effet sur la sé cré tion de l'hormone luté inisante (LH) et l'hormone folliculo-stimulante (FSH) [39]. Il est inté ressant de noter que l'expression et la distribution de FAAH, NAPE-PLD, CB1 et CB2 dans les tissus reproducteurs fé minins varient é galement avec le cycle menstruel, ce qui suggè re que l'expression du SEC est corré lé e aux fluctuations hormonales [40].…”
Section: Impact Du Cannabis Sur L'axe Hypothalamohypophysaireunclassified
“…Folliculogenesis [35,36] Oocyte maturation [35] Embryo transport [37] Embryo implantation/pregnancy [38][39][40][41] Endometrial plasticity [42] Delivery [34,43]…”
Section: Female Reproduction Referencesmentioning
confidence: 99%